Profile analysis and confunding for life quality: disabled people and race - Oliveira, Paulo Meira e Silva de (Brazilian Journal of Biometrics, 2023)
Disability means a physical, intellectual or sensory disability, permanent or temporary nature, which limits the ability to perform one or more activities. It is characterized as complex, dynamic and multidisciplinary. They are affected by poor health outcomes, lower educational attainment, lower economic participation, higher poverty rates, greater dependency and restriction on participation and inclusion. Racism is a behavior that is the result of aversion, hatred, towards people who have a racial resemblance that it is possible to observe, through traits such as skin color, hair type, it results from the belief in the existence of superior human races or types and inferior, in an attempt to impose itself as unique or true. Life Quality results from the relationship between biological, social and psychological factors and also from the integration between the individual and society, being transformed according to the period of life and the socio-cultural environment in which the individual is inserted. In terms of Brazil, the existence of these two situations can be noted that are subject to assistance from the public authorities, such as the quota laws for disabled people and for races the black, brown and indigenous. The objective of this work is to evaluate the effect for race, disability and the interaction between race and disability for the variable’s education, income and gender through a comparative study using descriptive analysis and experimental design for the 2010 Demographic Census data and that can contribute to a better life quality for these groups.